Kajian Aksesibilitas Kawasan Ekowisata di Kabupaten Kulon Progo - Maro, Junialorin Melania; Kurniati, Ayu Candra; Efendi, Hatta (Institut Teknologi Nasional Yogyakarta, 2023)
Spatial planning has an association with transportation where space is an activity which is placed on city land, while transportation is a network system that physically connects one activity space to other ones. Tourism is one of the areas designated for cultivation sectors. In addition to population and natural resources, transportation is one of the main components in terms of developing a region. Kulon Progo Regency develops tourism areas by dividing them into several KPPD and KSPD in accordance with the direction of tourism activities development. Kulon Progo has various natural tourism prospective ranging from coastal tourism, lowlands and mountains which have the potential to be integrated with water resource conservation according to the Kiskendo KSPD development plan. The development of tourism in a region requires several supporting factors, one of which is accessibility in reaching the location. Accessibility in finding a location is related to various factors that determine the level of ease and comfort in reaching a location. This research was conducted with the aim of knowing the level of accessibility in reaching ecotourism objects at the Kiskendo KSPD which is in Kapanewon Girimulyo. With two study targets, namely: (1) Identify accessibility in ecotourism areas and (2) Assess accessibility in ecotourism areas. The research was conducted using qualitative descriptive analysis and triangulation analysis. With the various variables used, the results showed that the level of accessibility in reaching ecotourism objects in Kapanewon Girimulyo scored in the